2019
DOI: 10.1007/978-3-030-19365-2_7
|View full text |Cite
|
Sign up to set email alerts
|

“My Treasure Box”: Pedagogical Documentation, Digital Portfolios and Children’s Agency in Finnish Early Years Education

Abstract: This chapter discusses the opportunities and challenges associated with the inclusive use of digital portfolios in pedagogical documentation in Finnish early childhood education (ECE), and examines children's participation and agency in the process. To this end, we draw on empirical data from the research and development programme of three Finnish municipalities and their ECE centres. Altogether, the empirical data comprise the digital portfolios of 71 children from six ECE groups each comprising of children a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
4
0
1
Order By: Relevance
“…No negative perceptions or disadvantages related to the use of e-portfolios for children were identified. Kumpulainen and Ouakrim-Soivio (2019) conducted an empirical research in Finnish ECE context to explore the opportunities and challenges of using digital portfolios and consistent with the opinions revealed in this study, their findings demonstrated that e-portfolios promoted the learning and developmental processes of children, highlighted their interests and emotions, and allowed rich and multi-faceted reflections of their activities.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…No negative perceptions or disadvantages related to the use of e-portfolios for children were identified. Kumpulainen and Ouakrim-Soivio (2019) conducted an empirical research in Finnish ECE context to explore the opportunities and challenges of using digital portfolios and consistent with the opinions revealed in this study, their findings demonstrated that e-portfolios promoted the learning and developmental processes of children, highlighted their interests and emotions, and allowed rich and multi-faceted reflections of their activities.…”
Section: Discussionsupporting
confidence: 68%
“…Knauf (2020) states that the challenge of implementing documentation is not limited to individual teachers or specific countries; it is also apparent on a global scale, despite the growing emphasis on documentation and the increased understanding of its impact. Kumpulainen and Ouakrim-Soivio (2019), who highlight the active involvement of children in creating and utilizing e-portfolios as pedagogical tools, stress the importance of teacher professionalism in supporting this process.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers need to implement a participatory pedagogy that empowers children's agency for the advancement of their learning and holistic development (Kumpulainen and Ouakrim-Soivio, 2019). In this discussion, we have framed the use of AaL in early childhood classrooms, with a focus on how the portfolio could be utilised as a valuable tool that has great potential to provide reflective opportunities for supporting children's learning.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, this article aims to stimulate a discussion about the suitability of AaL in early childhood classrooms, particularly through the use of portfolios. The concept of the portfolio as a participatory pedagogy in early childhood education (Kumpulainen and Ouakrim-Soivio, 2019) needs to be reframed with consideration of the role of children and the idea of AaL.…”
Section: Introductionmentioning
confidence: 99%
“…Die Organisation und Verwaltung der Daten funktioniere besser und dadurch würden Arbeitsprozesse erleichtert und beschleunigt werden (Burghardt und Knauf 2015b), was sich wiederum positiv auf die pädagogische Arbeit auswirken könnte (Holand, Reichert-Garschhammer, und Lorenz 2019). Beispielsweise könnten, durch Fotos und Videoaufnahmen, Lern-und Bildungsprozesse mithilfe von Apps besonders gut aufgezeigt werden (Kumpulainen und Ouakrim-Soivio 2019). Auch könnten Kinder sowie Eltern besser am Dokumentationsprozess partizipieren und die Kommunikation mit Eltern würde intensiviert (Einarsdóttir 2005;Gallagher 2018;Knauf 2020;Parnell und Bartlett 2012).…”
Section: Die Nutzung Von Dokumentations-apps In Kindertagesstättenunclassified